Overview of Community Knowledge, Attitudes, and Perceptions Regarding HIV and AIDS in the Working Area of Weliman Public Health Center, Malaka District - Nahak, Gregoria Luruk; Junias, Marylin Susanti; Setyobudi, Agus (Faculty of Public Health, Nusa Cendana University, 2024)
HIV (Human Immunodeficiency Virus) is a type of virus that infects white blood cells causing a decrease in human immunity. AIDS (Acquired immuno deficiency Syndrome) is a set of symptoms of diseases caused by HIV. Data from the Malacca Regency AIDS Commission where HIV and AIDS cases reached 157 people in 2021 and Puskesmas Weliman HIV and AIDS cases totaled 12 cases in 2021. This study aims to determine the picture of knowledge, attitudes and public perceptions about the incidence of HIV and AIDS in the working area of the Weliman Health Center of Malacca Regency. This type of research uses quantitative descriptive research methods. The population in this study is people who are in the working area of the Weliman Health Center of Malacca Regency based on the age of 25-50 years with a total of 5,271 people with a sample of 98 respondents.The instrument used is a questionnaire and the analysis is carried out quantitatively descriptive. The results showed that the picture of public knowledge about HIV and AIDS disease was categorized as good, the picture of public attitudes about HIV and AIDS disease was categorized as positive and the picture of public perception about HIV and AIDS disease was categorized as good. Some people do not understand about the prevention and transmission of the HIV virus. It is expected for health workers to carry out socialization or counseling activities to the community to increase public knowledge related to the transmission and prevention of HIV and AIDS